2018
DOI: 10.1080/17518423.2018.1437843
|View full text |Cite
|
Sign up to set email alerts
|

General movements and motor outcomes in two infants exposed to Zika virus: brief report

Abstract: GM assessment can be useful for ZIKV-exposed infants. These findings represent the first information on GMs and long-term motor outcomes in ZIKV-exposed infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(38 citation statements)
references
References 16 publications
0
38
0
Order By: Relevance
“…One unexpected observation was that the period on which symptoms of infection was described was not maintained in the final analytical model, as speculated by Soares‐Marangoni et al . This finding can be associated with the number of children whose mothers described the symptoms of infection in the third trimester of pregnancy, and with other facts, not analysed in this study, such as maternal immunity and viral charge.…”
Section: Discussionmentioning
confidence: 53%
“…One unexpected observation was that the period on which symptoms of infection was described was not maintained in the final analytical model, as speculated by Soares‐Marangoni et al . This finding can be associated with the number of children whose mothers described the symptoms of infection in the third trimester of pregnancy, and with other facts, not analysed in this study, such as maternal immunity and viral charge.…”
Section: Discussionmentioning
confidence: 53%
“…Traveller/non-traveller populations: In this update, we found further evidence that congenital abnormalities occurred in infants born to women travellers returning from ZIKV-affected areas and women remaining in those areas. In total, 25 publications report on 272 congenital abnormalities due to ZIKV infection in travellers 27, 29, 30, 32, 34, 36, 38, 42, 45, 56, 58, 61, 89, 94, 98, 109, 117, 122, 123, 137, 140, 151, 153, 166, 173 , with 109 publications reporting congenital abnormalities due to ZIKV in 2652 non travellers 2426, 28, 31, 33, 35, 37, 3941, 43, 44, 4648, 50, 51, 54, 57, 60, 6279, 81, 8385, 87, 88, 9093, 95– 97, 100, 101, 104– 106, 110113, 115, 116, 118, 119, 121, 124135, 142147, 149, 152, 154, 156164, 167, 168, 171, 172, 175180, 182, …”
Section: Resultsmentioning
confidence: 99%
“…A few studies have described the neurodevelopmental outcome so far using Bayley-III Scales of Infant and Toddler Development Test 6,19,20 and other scales, such as the Alberta Infant Motor Scale, 19,21 the Test of Infant Motor Performance, 22 Denver II, 23 and Gross Motor Function Measure. 9,24 These studies have demonstrated a similar pattern of severe developmental impairment in motor, cognitive, and language domains, but all with a shorter time of follow-up and with a smaller sample of microcephalic children than we reported here.…”
Section: Discussionmentioning
confidence: 99%